EXTH-84. TARGETING THE SALVAGE PATHWAY OF NAD+ GENERATION IN GLIOMAS BY KPT-9274, A NOVEL DUAL INHIBITOR OF PAK4 AND NAMPT. Issue 11 (6th November 2017) - Sharma, Pratibha; Kesanakurti, Divya; Wu, Pei-Jung; Xu, Jihong; Sampath, Deepa; Senapedis, William; Baloglu, Erkan; Puduvalli, Vinay K
Abstract: BACKGROUND: Current treatment of glioblastoma (GBM) with surgery and chemoRT yields an average survival of ~1.5 years, highlighting the need for more effective therapies. We have previously reported that PAK4 is a key modulator of radioresistance in GBM. Additionally, pathways that regulate differential energy metabolism in gliomas and circumvent tumor heterogeneity have recently emerged as promising therapeutic targets. We hypothesized that inhibition of NAMPT, the rate-limiting enzyme of the NAD+ salvage pathway, a key pathway preferentially used in glioma energy metabolism, would be effective against GBM. METHODS: We tested the efficacy of KPT9274, a potent first-in-class dual inhibitor of PAK4 and NAMPT, currently in human trials against solid tumors and lymphomas (NCT02702492), on NAD levels and cell viability in glioma cell lines and patient-derived glioma stem-like cells (GSC). We also examined enzyme-kinetics of various components of the NAD salvage pathway and effects of NADH rescue by nicotinamide, NMN and NAD. Lastly, we examined the biological relevance of NAMPT inhibition in glioma cells and GSC using a combination of cell adhesion, wound-healing, transwell-migration and microtubule formation assays. RESULTS: Treatment with KPT9274 resulted in potent depletion of NAD in glioma cells which was rescued by nicotinamide, NMN and NAD demonstrating its specificity against NAMPT. KPT-9274 treatment resulted in potent inhibition of cell adhesion, migration, cell invasion, endothelial tube formation and proliferation in glioma cells and GSC. In vivo studies in mouse bioluminescent intracranial glioma PDX model as well as PK studies are ongoing to confirm the pre-clinical significance of targeting NAMPT in gliomas and will be presented. CONCLUSIONS: Our study demonstrates a key role for NAMPT in NAD generation in gliomas as seen by the potent biological effects of KPT-9274 against these tumors and supports the potential for targeting the NAD salvage pathway as a novel therapeutic strategy for treatment of GBM.